Interface engineering induced Dzyaloshinskii-Moriya interaction enhancement in Py/Ti/CoFeB/MgO heterostructures - Song, Xiaoyue; Cao, Zhiqiang; Bai, Ligang; Zhao, Junbiao; Cai, Xudong; Zhu, Dapeng; Wei, Guodong (Frontiers in Electronics, 2025)
Dzyaloshinskii-Moriya interaction (DMI) is a key driver of chiral magnetism and has garnered significant interest in applied magnetism and spintronics. Interface engineering has been demonstrated to effectively enhance the DMI in many traditional heterostructures. The regulation of DMI is highly dependent on interface properties, which vary significantly across different material systems. Therefore, determining the optimal interface structure to maximize the DMI value presents a complex challenge. In this work, Brillouin light-scattering (BLS) spectroscopy quantitatively reveals a strong interfacial DMI of 17 μJ/m2 in Py/Ti (tTi)/CoFeB/MgO heterostructures with robust perpendicular magnetic anisotropy when the thickness of the Ti layer is 2 nm. Furthermore, we employed a field-modulated magneto-optical Kerr-effect microscope (MOKE) to visualize the existence of stable labyrinth domains in real space in the Py/Ti (2 nm)/CoFeB/MgO systems, which might be able to induce further skyrmions. By optimizing the thickness of a specific membrane configuration, this paper offers a critical materials foundation for advancing spintronics applications.